A fiber cloth-based polymer electrolyte and its preparation method and application

By using fiber cloth-based polymer electrolyte in solid-state lithium-ion batteries, the problem of poor contact between the electrode/electrolyte is solved, high room temperature ion conductivity and wide electrochemical stability window are achieved, and the cycle stability and safety of the battery are improved.

CN114914530BActive Publication Date: 2025-03-04GUANGDONG UNIV OF TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210681799.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-16
Publication Date
2025-03-04
Estimated Expiration
2042-06-16

AI Technical Summary

Technical Problem

In existing solid-state lithium-ion batteries, poor contact between the electrode/electrolyte interfaces leads to low ion conductivity and poor circulation performance, which poses safety hazards.

Method used

A solid electrolyte with high room temperature ion conductivity and wide electrochemical stability window was prepared by polymerizing ultrafine deny polypropylene fiber cloth and dioxycyclohexanone monomer through HClSO3 catalyst.

Benefits of technology

It achieves high room temperature ion conductivity and wide electrochemical stability window, which can effectively inhibit the growth of lithium dendrites and improve the stability of high-speed cycles. It is suitable for solid-state lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114914530B_ABST
    Figure CN114914530B_ABST
Patent Text Reader

Abstract

The present invention discloses a fiber cloth-based polymer electrolyte and its preparation method and application. In the present invention, COPET / PP island-in-sea fiber cloth is used to remove the sea component COPET with an alkaline solution to obtain an ultra-fine denier polypropylene fiber cloth as a support layer, and HClSO 3 The catalyst first initiates the preliminary polymerization of p-dioxanone monomer, and then lithium salt is added to prepare an electrolyte precursor; the electrolyte precursor is infiltrated into an ultrafine denier polypropylene fiber cloth base for further polymerization reaction to generate poly-p-dioxanone, so that the polymer electrolyte can be well supported on the fiber cloth base, and a fiber cloth-based polymer electrolyte is prepared. The fiber cloth-based polymer electrolyte of the present invention has high room temperature ionic conductivity, a wide electrochemical stability window, and can effectively inhibit the growth of lithium dendrites, improve high-rate (0.5-10C) cycle stability, and is particularly suitable for solid-state lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a fiber cloth-based polymer electrolyte and a preparation method and application thereof. Background Art

[0002] In recent decades, with the continuous consumption of fossil fuels, environmental pollution and the intensification of the greenhouse effect, efficient energy storage and conversion systems have been rapidly developed, and liquid lithium batteries are considered to be one of the most promising energy storage systems due to their high energy density and mature processing technology. However, due to the use of a large amount of liquid electrolyte, these liquid lithium batteries are susceptible to severe thermal effects and have certain safety hazards. Studies have shown that solid polymer electrolytes (SPE) or inorganic solid electrolytes (ISE) without a large amount of liquid solvent can significantly improve the safety characteristics of lithium batteries. Although some ion exchange electrodes exhibit high ionic conductivity at room temperature, their inherent fragility and extremely poor electrode / electrolyte contact greatly hinder their practical application.

[0003] At present, people are committed to the research of flexible SPE, such as ethylene oxide (PEO), polypropylene carbonate (PPC) and polyethylene carbonate (PEC) with sequential polar groups, but there is still the problem of poor electrode / electrolyte interface contact in solid-state lithium batteries. In order to obtain close interface contact between SPE and electrode, the existing technology adopts the solid-state lithium battery assembled by heating at medium and high temperatures, but most of the initiators used in the polymerization process will cause some undesirable parasitic reactions, resulting in the formation of poor solid electrolyte interface (SEI) layer, thereby deteriorating the cycle performance of the solid electrolyte. It can be seen that there is no solid electrolyte that can well meet the use requirements of solid-state lithium-ion batteries. Therefore, it is necessary to develop a new type of solid polymer electrolyte that can solve the problem of poor electrode / electrolyte interface contact, have high ionic conductivity at room temperature, and do not affect the cycle performance of the solid electrolyte, which is of great significance for the development of solid-state lithium-ion batteries. Summary of the invention

[0004] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a fiber cloth-based polymer electrolyte, a preparation method thereof, and a simple process. The fiber cloth-based polymer electrolyte prepared by the method of the present invention has high room temperature ionic conductivity, a wide electrochemical stability window, and can effectively inhibit the growth of lithium dendrites, improve high-rate (0.5~10C) cycle stability, and is particularly suitable for solid-state lithium-ion batteries.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing a fiber cloth-based polymer electrolyte comprises the following steps:

[0007] S1. Preparation of ultra-fine denier polypropylene fiber base: The COPET / PP sea-island type fiber cloth with polypropylene as the island component and polyethylene terephthalate as the sea component was soaked in an alkaline solution to remove the sea component COPET and dried to obtain an ultra-fine denier polypropylene fiber base;

[0008] S2. Preparation of electrolyte precursor: under inert atmosphere, add p-dioxanone monomer and HCLSO3 catalyst solution into a polymerization reaction vessel, stir evenly and heat to 40-80°C for constant temperature reaction for 1-4h to obtain a preliminary polymerization product, mix the preliminary polymerization product and lithium salt and stir evenly to obtain an electrolyte precursor;

[0009] S3. Preparation of fiber cloth-based polymer electrolyte: The electrolyte precursor prepared in step S2 is coated on the ultrafine denier polypropylene fiber cloth prepared in step S1, so that the electrolyte precursor is infiltrated into the fiber cloth, and the temperature is heated to 40-150°C, and further polymerization reaction is carried out until the electrolyte is completely polymerized into a solid, thereby obtaining a fiber cloth-based polymer electrolyte.

[0010] The present invention uses an ultra-fine denier polypropylene fiber cloth base as a support layer, firstly initiates the preliminary polymerization of p-dioxanone (PDO) monomers through an HClSO3 catalyst, and then adds a lithium salt to prepare an electrolyte precursor; the electrolyte precursor is infiltrated into the ultra-fine denier polypropylene fiber cloth base for further polymerization reaction, so that the polymer poly-p-dioxanone (PPDO) is in close contact with the fiber cloth base and can be well supported on the fiber cloth base, thereby obtaining a solid polymer electrolyte with high room temperature ionic conductivity and a wide electrochemical stability window.

[0011] The COPET / PP island-in-sea fiber cloth of the present invention is formed by cross-weaving of island-in-sea ultrafine denier fibers. The island-in-sea ultrafine denier fibers are composite fibers in which polypropylene (PP) is dispersed in polyethylene terephthalate (COPET). From the cross section of the fiber, PP is surrounded by COPET in a fine and dispersed state, that is, PP is in an "island" state and COPET is in a "sea" state. The island component and the sea component are continuously, densely and evenly distributed in the axial direction of the fiber. If the sea component is removed by a solvent, a bundle of ultrafine denier polypropylene fiber bundles can be obtained.

[0012] Polyethylene terephthalate is an alkali-soluble polyester, and the present invention uses an alkali solution to remove the sea component COPET in the fiber cloth. Preferably, in step S1, an 80-100°C alkali solution is used to soak the COPET / PP sea-island fiber cloth for 10-30 minutes; the alkali solution is selected from any one of a sodium hydroxide solution or a potassium hydroxide solution; and the concentration of the alkali solution is 15-30 g / L.

[0013] After removing the sea component structure in the COPET / PP island-in-sea fiber cloth, the island component ultrafine denier polypropylene fiber cloth is left, and there are certain gaps between the fibers, so that the fiber cloth has a dispersed porous structure, so that the polymer electrolyte can be carried on the fiber surface and in the gaps, thereby increasing its fit. The different proportions of the sea component will affect the size and distribution of the gaps between the fibers of the final ultrafine denier polypropylene fiber cloth base, thereby affecting the carrying effect of the polymer electrolyte. Preferably, the island component in the COPET / PP island-in-sea fiber cloth described in the present invention accounts for 60~70wt%, and the sea component accounts for 30~40wt%.

[0014] The structure of the polydioxanone is , where n=10-200.

[0015] The HS1SO3-catalyzed ring-opening polymerization reaction mechanism of the polydioxanone is as follows:

[0016]

[0017] HClSO3 dissociates hydrogen ions, triggering the formation of dioxanone monomers, generating active centers in the initiation reaction, and forming ion pairs with the reaction ions. The dioxanone monomers are continuously inserted between the active centers and the counterions, and the chain grows. Therefore, the counterions have sufficient nucleophilicity, and the growing active centers combine with the counterions to form covalent bonds and terminate.

[0018] Due to the presence of lithium salt, at high temperature, the unreacted active centers can coordinate with the anions in the lithium salt, further improving the conversion rate of dioxanone without parasitic reactions, effectively increasing the lithium ion migration number.

[0019] Preferably, the molar ratio of the dioxanone monomer to HClSO3 is (2000-2500):1.

[0020] Preferably, the molar ratio of the p-dioxanone monomer to the lithium salt is (1-15):1; more preferably, the molar ratio of the p-dioxanone monomer to the lithium salt is (3-12):1; further preferably, the molar ratio of the p-dioxanone monomer to the lithium salt is (5-9):1.

[0021] Preferably, the lithium salt is selected from any one or more of lithium tetrafluoroborate, lithium hexafluorophosphate, lithium perchlorate or lithium bis(oxalatoborate).

[0022] Preferably, the heating reaction time in step S3 is 6-24 hours.

[0023] The present invention also provides a fiber cloth-based polymer electrolyte, which is prepared by the preparation method of the fiber cloth-based polymer electrolyte.

[0024] The present invention also provides application of the fiber cloth-based polymer electrolyte in a solid-state lithium ion battery.

[0025] The present invention also provides a solid-state lithium-ion battery, comprising a positive electrode, a negative electrode and the fiber cloth-based polymer electrolyte of the present invention.

[0026] Preferably, the material of the positive electrode is selected from any one or more of lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide or lithium manganese nickel oxide.

[0027] Preferably, the material of the negative electrode is selected from any one or more of metallic lithium, metallic lithium alloy, natural graphite or nano-silicon material.

[0028] The present invention has the following beneficial effects:

[0029] The present invention uses an alkaline solution to remove the sea component COPET from COPET / PP sea-island fiber cloth to obtain an ultra-fine denier polypropylene fiber cloth as a support layer, which has excellent mechanical properties and can provide a good support structure; at the same time, HClSO3 catalyst is used to first initiate the preliminary polymerization of p-dioxanone monomer, and then lithium salt is added to prepare an electrolyte precursor; the electrolyte precursor is infiltrated into an ultra-fine denier polypropylene fiber cloth base for further polymerization reaction, and at high temperature, the unreacted active center can coordinate with the anion in the lithium salt, further improving the conversion rate of p-dioxanone, and reacting to generate poly-p-dioxanone; because the ultra-fine denier polypropylene fiber cloth base has a dispersed porous structure, the electrolyte precursor and the lithium salt can be well infiltrated into the fiber cloth base for reaction, thereby achieving the support of the polymer electrolyte on the fiber surface and in the gap, so that the polymer electrolyte and the fiber cloth base are in close contact, and the adhesion is increased; and the poly-p-dioxanone can dissolve the Li salt and act as a Li + The fiber cloth-based polymer electrolyte prepared by the method of the present invention has high room temperature ionic conductivity, a wide electrochemical stability window, and can effectively inhibit the growth of lithium dendrites and improve high rate (0.5~10C) cycle stability, and is particularly suitable for solid-state lithium-ion batteries.

[0030] During the preparation process of the fiber cloth-based polymer electrolyte of the present invention, the residual initiator is very small, no parasitic reaction occurs, the lithium ion migration number can be effectively increased, and a stable SEI layer is formed on the lithium metal anode, which has good cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of polydioxanone in Example 3. DETAILED DESCRIPTION

[0032] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0033] The reagents used in the examples and comparative examples of the present invention are all commercially available, but are not limited to these materials.

[0034] Embodiment 1:

[0035] S1. Preparation of ultra-fine denier polypropylene fiber cloth base: COPET / PP sea island fiber cloth with a sea component COPET accounting for 30wt% and an island component PP accounting for 70wt% was soaked in 15g / L sodium hydroxide solution at 100°C for 15min to remove the sea component COPET. The cloth was washed with deionized water and dried in an oven at 70°C to obtain an ultra-fine denier polypropylene fiber cloth base.

[0036] S2. Preparation of electrolyte precursor: In a glove box filled with argon, add p-dioxanone monomer and HClSO3 catalyst solution into a polymerization reaction bottle, heat to 40°C and stir evenly, and react at a constant temperature for 2 hours to obtain a preliminary polymerization product. The preliminary polymerization product and lithium hexafluorophosphate are mixed and stirred evenly to obtain an electrolyte precursor; wherein the molar ratio of p-dioxanone monomer to lithium hexafluorophosphate is 1:1; the molar ratio of p-dioxanone monomer to HClSO3 is 2500:1.

[0037] S3. Preparation of fiber cloth-based polymer electrolyte: The electrolyte precursor prepared in step S2 is evenly coated on the ultrafine denier polypropylene fiber cloth prepared in step S1 by a dip coater, so that the electrolyte precursor is infiltrated into the fiber cloth, and further polymerized in an oven at 90°C for 6 hours until the electrolyte is completely polymerized into a solid, thereby obtaining a fiber cloth-based polymer electrolyte.

[0038] Embodiment 2:

[0039] S1. Preparation of ultra-fine denier polypropylene fiber cloth base: COPET / PP sea island fiber cloth with a sea component COPET accounting for 30wt% and an island component PP accounting for 70wt% was soaked in 15g / L sodium hydroxide solution at 100°C for 15min to remove the sea component COPET. The cloth was washed with deionized water and dried in an oven at 70°C to obtain an ultra-fine denier polypropylene fiber cloth base.

[0040] S2. Preparation of electrolyte precursor: In a glove box filled with argon, add p-dioxanone monomer and HClSO3 catalyst solution into a polymerization reaction bottle, heat to 40°C and stir evenly, and react at a constant temperature for 2 hours to obtain a preliminary polymerization product. The preliminary polymerization product and lithium hexafluorophosphate are mixed and stirred evenly to obtain an electrolyte precursor; wherein the molar ratio of p-dioxanone monomer to lithium hexafluorophosphate is 3:1; the molar ratio of p-dioxanone monomer to HClSO3 is 2500:1.

[0041] S3. Preparation of fiber cloth-based polymer electrolyte: The electrolyte precursor prepared in step S2 is evenly coated on the ultrafine denier polypropylene fiber cloth prepared in step S1 by a dip coater, so that the electrolyte precursor is infiltrated into the fiber cloth, and further polymerized in an oven at 90°C for 6 hours until the electrolyte is completely polymerized into a solid, thereby obtaining a fiber cloth-based polymer electrolyte.

[0042] Embodiment 3:

[0043] S1. Preparation of ultra-fine denier polypropylene fiber cloth base: COPET / PP sea island fiber cloth with a sea component COPET accounting for 30wt% and an island component PP accounting for 70wt% was soaked in 15g / L sodium hydroxide solution at 100°C for 15min to remove the sea component COPET. The cloth was washed with deionized water and dried in an oven at 70°C to obtain an ultra-fine denier polypropylene fiber cloth base.

[0044] S2. Preparation of electrolyte precursor: In a glove box filled with argon, add p-dioxanone monomer and HClSO3 catalyst solution into a polymerization reaction bottle, heat to 40°C and stir evenly, and react at a constant temperature for 2 hours to obtain a preliminary polymerization product. The preliminary polymerization product and lithium hexafluorophosphate are mixed and stirred evenly to obtain an electrolyte precursor; wherein the molar ratio of p-dioxanone monomer to lithium hexafluorophosphate is 5:1; the molar ratio of p-dioxanone monomer to HClSO3 is 2500:1.

[0045] S3. Preparation of fiber cloth-based polymer electrolyte: The electrolyte precursor prepared in step S2 is evenly coated on the ultrafine denier polypropylene fiber cloth prepared in step S1 by a dip coater, so that the electrolyte precursor is infiltrated into the fiber cloth, and further polymerized in an oven at 90°C for 6 hours until the electrolyte is completely polymerized into a solid, thereby obtaining a fiber cloth-based polymer electrolyte.

[0046] Embodiment 4:

[0047] S1. Preparation of ultra-fine denier polypropylene fiber cloth base: COPET / PP sea island fiber cloth with a sea component COPET accounting for 30wt% and an island component PP accounting for 70wt% was soaked in 15g / L sodium hydroxide solution at 100°C for 15min to remove the sea component COPET. The cloth was washed with deionized water and dried in an oven at 70°C to obtain an ultra-fine denier polypropylene fiber cloth base.

[0048] S2. Preparation of electrolyte precursor: In a glove box filled with argon, add p-dioxanone monomer and HClSO3 catalyst solution into a polymerization reaction bottle, heat to 40°C and stir evenly, and react at a constant temperature for 2 hours to obtain a preliminary polymerization product. The preliminary polymerization product and lithium hexafluorophosphate are mixed and stirred evenly to obtain an electrolyte precursor; wherein the molar ratio of p-dioxanone monomer to lithium hexafluorophosphate is 7:1; the molar ratio of p-dioxanone monomer to HClSO3 is 2500:1.

[0049] S3. Preparation of fiber cloth-based polymer electrolyte: The electrolyte precursor prepared in step S2 is evenly coated on the ultrafine denier polypropylene fiber cloth prepared in step S1 by a dip coater, so that the electrolyte precursor is infiltrated into the fiber cloth, and further polymerized in an oven at 90°C for 6 hours until the electrolyte is completely polymerized into a solid, thereby obtaining a fiber cloth-based polymer electrolyte.

[0050] Embodiment 5:

[0051] S1. Preparation of ultra-fine denier polypropylene fiber cloth base: COPET / PP sea island fiber cloth with a sea component COPET accounting for 30wt% and an island component PP accounting for 70wt% was soaked in 15g / L sodium hydroxide solution at 100°C for 15min to remove the sea component COPET. The cloth was washed with deionized water and dried in an oven at 70°C to obtain an ultra-fine denier polypropylene fiber cloth base.

[0052] S2. Preparation of electrolyte precursor: In a glove box filled with argon, add p-dioxanone monomer and HClSO3 catalyst solution into a polymerization reaction bottle, heat to 40°C and stir evenly, and react at a constant temperature for 2 hours to obtain a preliminary polymerization product. The preliminary polymerization product and lithium hexafluorophosphate are mixed and stirred evenly to obtain an electrolyte precursor; wherein the molar ratio of p-dioxanone monomer to lithium hexafluorophosphate is 9:1; the molar ratio of p-dioxanone monomer to HClSO3 is 2500:1.

[0053] S3. Preparation of fiber cloth-based polymer electrolyte: The electrolyte precursor prepared in step S2 is evenly coated on the ultrafine denier polypropylene fiber cloth prepared in step S1 by a dip coater, so that the electrolyte precursor is infiltrated into the fiber cloth, and further polymerized in an oven at 90°C for 6 hours until the electrolyte is completely polymerized into a solid, thereby obtaining a fiber cloth-based polymer electrolyte.

[0054] Embodiment 6:

[0055] S1. Preparation of ultra-fine denier polypropylene fiber cloth base: COPET / PP sea island fiber cloth with a sea component COPET accounting for 30wt% and an island component PP accounting for 70wt% was soaked in 15g / L sodium hydroxide solution at 100°C for 15min to remove the sea component COPET. The cloth was washed with deionized water and dried in an oven at 70°C to obtain an ultra-fine denier polypropylene fiber cloth base.

[0056] S2. Preparation of electrolyte precursor: In a glove box filled with argon, add p-dioxanone monomer and HClSO3 catalyst solution into a polymerization reaction bottle, heat to 40°C and stir evenly, and react at a constant temperature for 2 hours to obtain a preliminary polymerization product. The preliminary polymerization product and lithium hexafluorophosphate are mixed and stirred evenly to obtain an electrolyte precursor; wherein the molar ratio of p-dioxanone monomer to lithium hexafluorophosphate is 12:1; the molar ratio of p-dioxanone monomer to HClSO3 is 2500:1.

[0057] S3. Preparation of fiber cloth-based polymer electrolyte: The electrolyte precursor prepared in step S2 is evenly coated on the ultrafine denier polypropylene fiber cloth prepared in step S1 by a dip coater, so that the electrolyte precursor is infiltrated into the fiber cloth, and further polymerized in an oven at 90°C for 6 hours until the electrolyte is completely polymerized into a solid, thereby obtaining a fiber cloth-based polymer electrolyte.

[0058] Embodiment 7:

[0059] S1. Preparation of ultra-fine denier polypropylene fiber cloth base: COPET / PP sea island fiber cloth with a sea component COPET accounting for 30wt% and an island component PP accounting for 70wt% was soaked in 15g / L sodium hydroxide solution at 100°C for 15min to remove the sea component COPET. The cloth was washed with deionized water and dried in an oven at 70°C to obtain an ultra-fine denier polypropylene fiber cloth base.

[0060] S2. Preparation of electrolyte precursor: In a glove box filled with argon, add p-dioxanone monomer and HClSO3 catalyst solution into a polymerization reaction bottle, heat to 40°C and stir evenly, and react at a constant temperature for 2 hours to obtain a preliminary polymerization product. The preliminary polymerization product and lithium hexafluorophosphate are mixed and stirred evenly to obtain an electrolyte precursor; wherein the molar ratio of p-dioxanone monomer to lithium hexafluorophosphate is 15:1; the molar ratio of p-dioxanone monomer to HClSO3 is 2500:1.

[0061] S3. Preparation of fiber cloth-based polymer electrolyte: The electrolyte precursor prepared in step S2 is evenly coated on the ultrafine denier polypropylene fiber cloth prepared in step S1 by a dip coater, so that the electrolyte precursor is infiltrated into the fiber cloth, and further polymerized in an oven at 90°C for 6 hours until the electrolyte is completely polymerized into a solid, thereby obtaining a fiber cloth-based polymer electrolyte.

[0062] Embodiment 8:

[0063] S1. Preparation of ultra-fine denier polypropylene fiber cloth base: COPET / PP sea island fiber cloth with a sea component COPET accounting for 30wt% and an island component PP accounting for 70wt% was soaked in 15g / L sodium hydroxide solution at 100°C for 15min to remove the sea component COPET. The cloth was washed with deionized water and dried in an oven at 70°C to obtain an ultra-fine denier polypropylene fiber cloth base.

[0064] S2. Preparation of electrolyte precursor: In a glove box filled with argon, add p-dioxanone monomer and HClSO3 catalyst solution into a polymerization reaction bottle, heat to 40°C and stir evenly, and react at a constant temperature for 2 hours to obtain a preliminary polymerization product. The preliminary polymerization product and lithium hexafluorophosphate are mixed and stirred evenly to obtain an electrolyte precursor; wherein the molar ratio of p-dioxanone monomer to lithium hexafluorophosphate is 15:1; the molar ratio of p-dioxanone monomer to HClSO3 is 2500:1.

[0065] S3. Preparation of fiber cloth-based polymer electrolyte: The electrolyte precursor prepared in step S2 is evenly coated on the ultrafine denier polypropylene fiber cloth prepared in step S1 by a dip coater, so that the electrolyte precursor is infiltrated into the fiber cloth, and further polymerized in an oven at 100°C for 24 hours until the electrolyte is completely polymerized into a solid, thereby obtaining a fiber cloth-based polymer electrolyte.

[0066] Embodiment 9:

[0067] S1. Preparation of ultra-fine denier polypropylene fiber cloth base: COPET / PP sea island fiber cloth with a sea component COPET accounting for 30wt% and an island component PP accounting for 70wt% was soaked in 15g / L sodium hydroxide solution at 100°C for 15min to remove the sea component COPET. The cloth was washed with deionized water and dried in an oven at 70°C to obtain an ultra-fine denier polypropylene fiber cloth base.

[0068] S2. Preparation of electrolyte precursor: In a glove box filled with argon, add p-dioxanone monomer and HClSO3 catalyst solution into a polymerization reaction bottle, heat to 40°C and stir evenly, and react at a constant temperature for 2 hours to obtain a preliminary polymerization product. The preliminary polymerization product and lithium hexafluorophosphate are mixed and stirred evenly to obtain an electrolyte precursor; wherein the molar ratio of p-dioxanone monomer to lithium hexafluorophosphate is 5:1; the molar ratio of p-dioxanone monomer to HClSO3 is 2500:1.

[0069] S3. Preparation of fiber cloth-based polymer electrolyte: The electrolyte precursor prepared in step S2 is evenly coated on the ultrafine denier polypropylene fiber cloth prepared in step S1 by a dip coater, so that the electrolyte precursor is infiltrated into the fiber cloth, and further polymerized in an oven at 40°C for 6 hours until the electrolyte is completely polymerized into a solid, thereby obtaining a fiber cloth-based polymer electrolyte.

[0070] Embodiment 10:

[0071] S1. Preparation of ultra-fine denier polypropylene fiber cloth base: COPET / PP sea island fiber cloth with a sea component COPET accounting for 30wt% and an island component PP accounting for 70wt% was soaked in 15g / L sodium hydroxide solution at 100°C for 15min to remove the sea component COPET. The cloth was washed with deionized water and dried in an oven at 70°C to obtain an ultra-fine denier polypropylene fiber cloth base.

[0072] S2. Preparation of electrolyte precursor: In a glove box filled with argon, add p-dioxanone monomer and HClSO3 catalyst solution into a polymerization reaction bottle, heat to 40°C and stir evenly, and react at a constant temperature for 2 hours to obtain a preliminary polymerization product. The preliminary polymerization product and lithium hexafluorophosphate are mixed and stirred evenly to obtain an electrolyte precursor; wherein the molar ratio of p-dioxanone monomer to lithium hexafluorophosphate is 5:1; the molar ratio of p-dioxanone monomer to HClSO3 is 2500:1.

[0073] S3. Preparation of fiber cloth-based polymer electrolyte: The electrolyte precursor prepared in step S2 is evenly coated on the ultrafine denier polypropylene fiber cloth prepared in step S1 by a dip coater, so that the electrolyte precursor is infiltrated into the fiber cloth, and further polymerized in an oven at 150°C for 6 hours until the electrolyte is completely polymerized into a solid, thereby obtaining a fiber cloth-based polymer electrolyte.

[0074] Embodiment 11:

[0075] S1. Preparation of ultra-fine denier polypropylene fiber cloth base: COPET / PP sea island fiber cloth with a sea component COPET accounting for 30wt% and an island component PP accounting for 70wt% was soaked in 15g / L sodium hydroxide solution at 100°C for 15min to remove the sea component COPET. The cloth was washed with deionized water and dried in an oven at 70°C to obtain an ultra-fine denier polypropylene fiber cloth base.

[0076] S2. Preparation of electrolyte precursor: In a glove box filled with argon, add p-dioxanone monomer and HClSO3 catalyst solution into a polymerization reaction bottle, heat to 80°C and stir evenly, and react at a constant temperature for 2 hours to obtain a preliminary polymerization product. The preliminary polymerization product and lithium hexafluorophosphate are mixed and stirred evenly to obtain an electrolyte precursor; wherein the molar ratio of p-dioxanone monomer to lithium hexafluorophosphate is 5:1; the molar ratio of p-dioxanone monomer to HClSO3 is 2500:1.

[0077] S3. Preparation of fiber cloth-based polymer electrolyte: The electrolyte precursor prepared in step S2 is evenly coated on the ultrafine denier polypropylene fiber cloth prepared in step S1 by a dip coater, so that the electrolyte precursor is infiltrated into the fiber cloth, and further polymerized in an oven at 90°C for 6 hours until the electrolyte is completely polymerized into a solid, thereby obtaining a fiber cloth-based polymer electrolyte.

[0078] Embodiment 12:

[0079] S1. Preparation of ultra-fine denier polypropylene fiber cloth base: COPET / PP sea island fiber cloth with a sea component COPET accounting for 30wt% and an island component PP accounting for 70wt% was soaked in 15g / L sodium hydroxide solution at 100°C for 15min to remove the sea component COPET. The cloth was washed with deionized water and dried in an oven at 70°C to obtain an ultra-fine denier polypropylene fiber cloth base.

[0080] S2. Preparation of electrolyte precursor: In a glove box filled with argon, add p-dioxanone monomer and HClSO3 catalyst solution into a polymerization reaction bottle, heat to 60°C and stir evenly, and react at a constant temperature for 1 hour to obtain a preliminary polymerization product. The preliminary polymerization product and lithium tetrafluoroborate are mixed and stirred evenly to obtain an electrolyte precursor; wherein the molar ratio of p-dioxanone monomer to lithium tetrafluoroborate is 8:1; the molar ratio of p-dioxanone monomer to HClSO3 is 2000:1.

[0081] S3. Preparation of fiber cloth-based polymer electrolyte: The electrolyte precursor prepared in step S2 is evenly coated on the ultrafine denier polypropylene fiber cloth prepared in step S1 by a dip coater, so that the electrolyte precursor is infiltrated into the fiber cloth, and further polymerized in an oven at 100°C for 24 hours until the electrolyte is completely polymerized into a solid, thereby obtaining a fiber cloth-based polymer electrolyte.

[0082] Comparative Example 1:

[0083] S1. Preparation of ultra-fine denier polypropylene fiber cloth base: COPET / PP sea island fiber cloth with a sea component COPET accounting for 30wt% and an island component PP accounting for 70wt% was soaked in 15g / L sodium hydroxide solution at 100°C for 15min to remove the sea component COPET. The cloth was washed with deionized water and dried in an oven at 70°C to obtain an ultra-fine denier polypropylene fiber cloth base.

[0084] S2. Preparation of electrolyte precursor: In a glove box filled with argon, add p-dioxanone monomer and HClSO3 catalyst solution into a polymerization reaction bottle, and react at 25°C for 2 hours to obtain a preliminary polymerization product. The preliminary polymerization product and lithium hexafluorophosphate are mixed and stirred to obtain an electrolyte precursor; wherein the molar ratio of p-dioxanone monomer to lithium hexafluorophosphate is 5:1; the molar ratio of p-dioxanone monomer to HClSO3 is 2500:1.

[0085] S3. Preparation of fiber cloth-based polymer electrolyte: The electrolyte precursor prepared in step S2 is evenly coated on the ultrafine denier polypropylene fiber cloth prepared in step S1 by a dip coater, so that the electrolyte precursor is infiltrated into the fiber cloth, and further polymerized in an oven at 90°C for 6 hours until the electrolyte is completely polymerized into a solid, thereby obtaining a fiber cloth-based polymer electrolyte.

[0086] Comparative Example 2:

[0087] S1. Preparation of ultra-fine denier polypropylene fiber cloth base: COPET / PP sea island fiber cloth with a sea component COPET accounting for 30wt% and an island component PP accounting for 70wt% was soaked in 15g / L sodium hydroxide solution at 100°C for 15min to remove the sea component COPET. The cloth was washed with deionized water and dried in an oven at 70°C to obtain an ultra-fine denier polypropylene fiber cloth base.

[0088] S2. Preparation of electrolyte precursor: In a glove box filled with argon, add p-dioxanone monomer and HClSO3 catalyst solution into a polymerization reaction bottle, heat to 40°C and stir evenly, and react at a constant temperature for 2 hours to obtain a preliminary polymerization product, which is an electrolyte precursor; the molar ratio of p-dioxanone monomer to HClSO3 is 2500:1.

[0089] S3. Preparation of fiber cloth-based polymer electrolyte: The electrolyte precursor prepared in step S2 is evenly coated on the ultrafine denier polypropylene fiber cloth prepared in step S1 by a dip coater, so that the electrolyte precursor is infiltrated into the fiber cloth, and further polymerized in an oven at 90°C for 6 hours until the electrolyte is completely polymerized into a solid, thereby obtaining a fiber cloth-based polymer electrolyte.

[0090] Comparative Example 3:

[0091] In a glove box filled with argon, add p-dioxanone monomer and HClSO3 catalyst solution into a polymerization reaction bottle, heat to 40°C and stir evenly, and react at a constant temperature for 2 hours to obtain a preliminary polymerization product. The preliminary polymerization product and lithium salt are mixed and stirred evenly to obtain an electrolyte precursor; wherein the molar ratio of p-dioxanone monomer to lithium salt is 5:1; the molar ratio of p-dioxanone monomer to HClSO3 is 2500:1.

[0092] The prepared electrolyte precursor was evenly coated on the Japanese NKK TF4530 cellulose membrane (organic system superelectric diaphragm) by a dip coater, so that the electrolyte precursor was infiltrated into the fiber cloth base, and further polymerized in an oven at 90°C for 6 hours until the electrolyte was completely polymerized into a solid to obtain a polymer electrolyte.

[0093] Comparative Example 4:

[0094] In a glove box filled with argon, add p-dioxanone monomer and HClSO3 catalyst solution into a polymerization reaction bottle, heat to 40°C and stir evenly, and react at a constant temperature for 2 hours to obtain a preliminary polymerization product. The preliminary polymerization product and lithium salt are mixed and stirred evenly to obtain an electrolyte precursor; wherein the molar ratio of p-dioxanone monomer to lithium salt is 5:1; the molar ratio of p-dioxanone monomer to HClSO3 is 2500:1.

[0095] The prepared electrolyte precursor was evenly coated on a commercial PP film (Shenzhen Xingyuan) by a dip coater, so that the electrolyte precursor was infiltrated into the fiber cloth base, and further polymerized in an oven at 90°C for 6 hours until the electrolyte was completely polymerized into a solid to obtain a polymer electrolyte.

[0096] The relevant performance tests are as follows:

[0097] (1) The polydioxanone in the fiber cloth-based polymer electrolyte of each example was characterized by hydrogen nuclear magnetic resonance spectroscopy. Figure 1 The nuclear magnetic resonance hydrogen spectrum of Example 3 has chemical shifts of 4.33 (2H, t), 4.16 (2H, t), and 3.78 (2H, t) ppm, respectively, indicating that the residual amount of initiator is very small. The characterization results of the other examples are the same as those of Example 3.

[0098] (2) The polymer electrolytes prepared in the examples and comparative examples were assembled into batteries and the following tests were performed:

[0099] ① Room temperature ionic conductivity: Assemble stainless steel sheet / polymer electrolyte / stainless steel sheet button cell, and use VMP3B-10 electrochemical workstation (Bio-Logic Science Instruments) electrochemical impedance spectroscopy (EIS) mode to test bulk resistance, where the disturbance voltage amplitude is 5mV and the frequency is 10mHz~1MHz. The relationship between bulk resistance and ionic conductivity is calculated as follows:

[0100]

[0101] Where δ is the ionic conductivity of the polymer electrolyte (S / cm); L0 is the thickness of the separator (cm); R b is the bulk resistance of the polymer electrolyte (Ω); S is the effective contact area between the polymer electrolyte and the stainless steel sheet (cm 2 ).

[0102] ② Electrochemical stability window: For the assembled stainless steel sheet / fiber cloth-based polymer electrolyte / lithium sheet button cell, a VMP3 electrochemical workstation was used to perform cyclic voltammetry scanning and record the electrochemical stability window.

[0103] ③ High cycle capacity retention rate: 100 cycle capacity retention rate at 5C.

[0104] Table 1: Test results of relevant properties of polymer electrolytes of Examples and Comparative Examples

[0105] <![CDATA[Room temperature ionic conductivity / S·cm -1 > Electrochemical stable window / V High cycle capacity retention Example 1 <![CDATA[4.23×10 -4 ]]> 5.05 91% Example 2 <![CDATA[5.71×10 -4 ]]> 5.21 92% Example 3 <![CDATA[7.28×10 -4 ]]> 5.09 92% Example 4 <![CDATA[6.53×10 -4 ]]> 5.12 92% Example 5 <![CDATA[6.17×10 -4 ]]> 5.15 93% Example 6 <![CDATA[6.07×10 -4 ]]> 5.15 92% Example 7 <![CDATA[5.82×10 -4 ]]> 5.08 91% Example 8 <![CDATA[6.07×10 -4 ]]> 5.11 91% Example 9 <![CDATA[5.15×10 -4 ]]> 4.95 89% Example 10 <![CDATA[5.52×10 -4 ]]> 5.07 90% Embodiment 11 <![CDATA[4.78×10 -4 ]]> 4.96 89% Example 12 <![CDATA[5.66×10 -4 ]]> 4.92 88% Comparative Example 1 <![CDATA[3.24×10 -5 ]]> 4.71 86% Comparative Example 2 <![CDATA[2.52×10 -5 ]]> 4.75 84% Comparative Example 3 <![CDATA[3.12×10 -4 ]]> 4.83 88% Comparative Example 4 <![CDATA[3.17×10 -4 ]]> 4.77 88%

[0106] The above results show that the fiber cloth-based polymer electrolyte prepared by the method of the present invention has high room temperature ionic conductivity, a wide electrochemical stability window, and high rate cycle stability.

Claims

1. A method for preparing a fiber cloth-based polymer electrolyte, characterized in that: The following steps are involved: S1. Preparation of ultra-fine denier polypropylene fiber cloth base: COPET / PP sea-island type fiber cloth with polypropylene as island component and polyethylene terephthalate as sea component is soaked in an alkaline solution to remove the sea component COPET, and dried to obtain an ultra-fine denier polypropylene fiber cloth base, wherein the island component accounts for 60-70wt% and the sea component accounts for 30-40wt% in the COPET / PP sea-island type fiber cloth; S2. Preparation of electrolyte precursor: under inert atmosphere, add p-dioxanone monomer and HClSO3 catalyst solution into a polymerization reaction vessel, heat to 40-80°C and stir evenly, react at constant temperature for 1-4h to obtain a preliminary polymerization product, mix the preliminary polymerization product and lithium salt and stir evenly to obtain an electrolyte precursor; S3. Preparation of fiber cloth-based polymer electrolyte: The electrolyte precursor prepared in step S2 is coated on the ultrafine denier polypropylene fiber cloth prepared in step S1, so that the electrolyte precursor is infiltrated into the fiber cloth, and the temperature is heated to 40-150°C, and further polymerization reaction is carried out until the electrolyte is completely polymerized into a solid, thereby obtaining a fiber cloth-based polymer electrolyte.

2. The method for preparing a fiber cloth-based polymer electrolyte according to claim 1, characterized in that: In step S1, the COPET / PP sea-island fiber cloth is soaked in an alkaline solution at 80-100° C. for 10-30 minutes; the alkaline solution is selected from any one of a sodium hydroxide solution and a potassium hydroxide solution; and the concentration of the alkaline solution is 15-30 g / L.

3. The method for preparing a fiber cloth-based polymer electrolyte according to claim 1, characterized in that: The molar ratio of the dioxanone monomer to HClSO3 is (2000-2500):

1.

4. The method for preparing a fiber cloth-based polymer electrolyte according to claim 1, characterized in that: The molar ratio of the dioxanone monomer to the lithium salt is (1-15):

1.

5. The method for preparing a fiber cloth-based polymer electrolyte according to claim 4, characterized in that: The molar ratio of the dioxanone monomer to the lithium salt is (3-12):

1.

6. The method for preparing a fiber cloth-based polymer electrolyte according to claim 5, characterized in that: The molar ratio of the dioxanone monomer to the lithium salt is (5-9):

1.

7. The method for preparing a fiber cloth-based polymer electrolyte according to claim 1, characterized in that: The lithium salt is selected from any one or more of lithium tetrafluoroborate, lithium hexafluorophosphate, lithium perchlorate or lithium bis(oxalatoborate).

8. The method for preparing a fiber cloth-based polymer electrolyte according to claim 1, characterized in that: The heating reaction time in step S3 is 6-24h.

9. A fiber cloth-based polymer electrolyte, characterized in that: The polymer electrolyte is prepared by the method for preparing the fiber cloth-based polymer electrolyte according to any one of claims 1 to 7.

10. Use of the fiber cloth-based polymer electrolyte according to claim 9 in a solid-state lithium-ion battery.

11. A solid-state lithium-ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode and the fiber cloth-based polymer electrolyte as claimed in claim 8.

Citation Information

Patent Citations

  • A biodegradable composite solid electrolyte membrane and a preparation method thereof

    CN109037766A

  • Solid electrolyte and preparation method thereof and lithium ion battery

    CN111900468A